(untitled) - AINI, NURUL (LATERNE, 2013)
One of language which is studied in Indonesia is German. Based on interviews with German teacher on SMA 1 Krian obtained explanations that the students tend to be passive when they sudied German especially speaking. Students always think is a difficult foreign language lessons. In connection with the effort to create a teaching and learning strategy that fun, teachers take advantage of the game. Playing monopoly on learning the German language would probably make students will be more active. This study aimed to describe the form of the game of Monopoly to practice conversational skills in German and describes strategies exploit monopoly game to practice conversational skills in German class XI High School. Keywords: conversation skills, the game Monopoly.